Liquid-state shrinkage aluminum electrolytic capacitor
By using multi-stage frequency conversion to corrode aluminum foil and Al2O3-TiO2 composite foil and optimized electrolyte and electrolytic paper in aluminum electrolytic capacitors, the problem of capacitor size reduction is solved, miniaturization is achieved without changing performance, and cost is reduced Space occupancy.
Patent Information
- Application Number
- CN202411417249.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-03
AI Technical Summary
How to reduce the size of the capacitor to meet the miniaturization needs of electronic equipment while keeping the voltage and capacity of the aluminum electrolytic capacitor unchanged.
Using multi-stage frequency conversion corrosion aluminum foil and Al2O3-TiO2 composite foil as electrodes, using electrolyte with GBL or glycol system, optimize the material and structure of electrolytic paper and sealant plugs, and through optical foil-multi-stage frequency conversion corrosion-multi-stage transformation The processing process prepares the anode foil, and controls the moisture content and conductivity in the electrolyte, and combines low-pressure transformation into a guide needle and high-tight Manila hemp fiber electrolytic paper to ensure the performance and reliability of the capacitor.
The size of aluminum electrolytic capacitors is reduced by more than 20%, reducing the use space and cost of electronic equipment lines, and ensuring the performance and life of capacitors.
Smart Images

Figure CN119252666A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum electrolytic capacitors, and in particular to a liquid shrink aluminum electrolytic capacitor. Background Art
[0002] Aluminum electrolytic capacitors are a common device in electronic circuits. Their working principle is to use the aluminum oxide film formed on the surface of the anode aluminum foil as a dielectric to form a capacitor by electrolysis. This type of capacitor has the characteristics of large capacity, high voltage, low ESR (equivalent series resistance) and long life. It is widely used in frequency converters, wind power converters, solar inverters, professional power supply equipment, uninterruptible power supplies, medical applications, professional photography equipment and automotive applications. Aluminum electrolytic capacitors play electrical roles such as filtering, bypassing, coupling, decoupling, and phase transfer. The basic parameters include operating voltage value, capacitance, size, etc. With the development of science and technology, electronic equipment circuits tend to be miniaturized. At the same time, companies have higher requirements for cost control, and the miniaturization of electronic components will also become a trend.
[0003] With the advancement of technology, a variety of miniaturized aluminum electrolytic capacitor products have appeared on the market. These products usually have higher voltage levels, smaller sizes and longer lifespans, and are suitable for applications with strict space requirements, such as smartphones, laptops, server power supplies and new energy vehicles.
[0004] Liquid aluminum electrolytic capacitors use the aluminum oxide film formed on the surface of aluminum foil as a dielectric and are formed by electrolysis. This type of capacitor has the advantages of small size, large capacity, excellent frequency response, and good temperature stability. It is widely used in power supply filtering, amplifier circuit coupling, signal voltage division, and timing circuits.
[0005] The structure of liquid aluminum electrolytic capacitors mainly includes metal shell, electrolyte, metal foil and sealing material. The metal shell is usually made of aluminum, and the electrolyte is an electrolyte solution, such as aluminum sulfate or aluminum hydroxide. The metal foil is electrochemically oxidized to form an aluminum oxide layer, which serves as the electrode of the capacitor. The sealing material is used to protect the internal components of the capacitor from external interference and damage.
[0006] The miniaturization technology of liquid aluminum electrolytic capacitors is constantly improving, and the launch of new products needs to meet the market demand for smaller size, higher performance and longer life capacitors. As electronic devices develop towards smaller, more efficient and more environmentally friendly directions, the market prospects for miniaturized liquid aluminum electrolytic capacitors are promising. Summary of the invention
[0007] The technical problem to be solved by the present invention is how to reduce the size of the capacitor while keeping the capacitance voltage and capacity of the aluminum electrolytic capacitor unchanged.
[0008] In order to solve the above problems, the present invention proposes the following technical solutions:
[0009] The present invention provides a liquid shrink aluminum electrolytic capacitor, comprising an anode foil, a cathode foil, an electrolyte and electrolytic paper;
[0010] The anode foil is a multi-stage frequency conversion corrosion aluminum foil;
[0011] The cathode foil is an Al2O3-TiO2 composite foil;
[0012] The water content of the electrolyte is ≤2% and the conductivity is ≥13ms / cm;
[0013] The thickness of the electrolytic paper is 30-50 μm, and the density is 0.30-0.50 g / cm 3 ;
[0014] The working voltage of the liquid shrink aluminum electrolytic capacitor is ≤25WV.
[0015] A further technical solution is that it also includes a guide needle, wherein the guide needle is a low-voltage forming guide needle, and the forming voltage is ≥140V.
[0016] A further technical solution is that the electrolyte is a GBL system electrolyte or an ethylene glycol system electrolyte.
[0017] A further technical solution is that the electrolytic paper is made of Manila hemp fiber.
[0018] A further technical solution is that the liquid shrinkage aluminum electrolytic capacitor also includes a sealing rubber plug, and after the sealing rubber plug is placed in an environment of 125° C. for 48 hours, the change in hardness of the rubber plug does not exceed 5%.
[0019] A further technical solution is that the sealing rubber plug contains IIR with a mass fraction of ≥30%.
[0020] A further technical solution is that the preparation process of the anode foil includes: plain foil - multi-stage variable frequency etching - multi-stage chemical formation treatment; wherein, when the multi-stage variable frequency etching process is performed, the frequency range of the alternating current is between 5 and 40 Hz, and the frequency values of each stage are different from each other.
[0021] A further technical solution is that the light foil process stage also includes annealing treatment, and the annealing temperature is 400-500°C.
[0022] A further technical solution is that the Al2O3-TiO2 composite foil is obtained by coating TiO2 nanoparticles on the surface of aluminum corrosion foil.
[0023] A further technical solution is that for a liquid reduced aluminum electrolytic capacitor with a working voltage of 25WV and a capacitance of 100μF, its diameter×height dimensions are less than 6.3mm×11mm; for a liquid reduced aluminum electrolytic capacitor with a working voltage of 16WV and a capacitance of 470μF, its diameter×height dimensions are less than 8mm×10.5mm.
[0024] Compared with the prior art, the technical effects achieved by the present invention include:
[0025] The liquid shrinkable aluminum electrolytic capacitor provided by the present invention can reduce the size of the aluminum electrolytic capacitor by more than 20% while keeping the voltage and capacity of the aluminum electrolytic capacitor unchanged, thereby reducing the use space and the circuit cost of the electronic equipment. The present invention can ensure miniaturization without sacrificing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.
[0027] Figure 1 The present invention provides a schematic diagram of the expanded structure of the capacitor core of the liquid shrinkable aluminum electrolytic capacitor.
[0028] Figure 2 This is a schematic structural diagram of the liquid shrinkable aluminum electrolytic capacitor provided by the present invention.
[0029] Reference numerals
[0030] 1 cathode foil, 2 anode foil, 3 electrolytic paper, 4 guide needle, 41 positive guide needle, 42 negative guide needle, 5 sealing rubber plug, 6 aluminum shell, 7 sleeve, 10 capacitor core. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Similar component numbers in the drawings represent similar components. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0033] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.
[0034] See also Figure 1 The embodiment of the present invention provides a liquid shrink aluminum electrolytic capacitor. From the unfolded structure diagram of the capacitor core, it includes an anode foil 2, a cathode foil 1, an electrolyte, an electrolytic paper 3 and a guide pin 4. The following specifically introduces each component:
[0035] The anode foil described in the embodiment of the present invention is a multi-stage frequency conversion etched aluminum foil.
[0036] Specifically, the preparation process of the anode foil of the embodiment of the present invention includes: plain foil - multi-stage variable frequency corrosion - multi-stage chemical formation treatment. Among them, the plain foil is a high-purity aluminum foil with a purity greater than 99.95% to ensure the performance of the capacitor. The process stage of plain foil preparation mainly includes steps such as melting, hot rolling, cold rolling, annealing and slitting. The annealing temperature is 400-500°C. The plain foil annealed within this temperature range can obtain a finished anode foil with a higher specific capacitance after corrosion and chemical formation when the plain foil of the same thickness is used.
[0037] Furthermore, after the plain foil is prepared, the surface oil and oxide film of the plain foil are removed, and then a multi-stage variable frequency etching process is performed to obtain the corroded foil. The principle is to form a microporous structure on the surface of the plain foil to increase its surface area, thereby increasing the electrostatic capacity of the capacitor. Specifically, in the present invention, during the AC electrolytic etching process, the aluminum foil is treated in a mixed solution composed of sulfuric acid and hydrochloric acid, the treatment temperature is controlled at 25 to 60°C, and the current density is 20 to 100A / dm 2 The power is controlled between 800~8000C / dm 2 The frequency values of each level of AC electrolytic corrosion are different from each other, and the frequency range is between 5 and 40 Hz. Through this multi-level variable frequency corrosion process, aluminum foil with high specific capacitance and excellent mechanical properties can be produced, which is more suitable for the use of aluminum electrolytic capacitors. The present invention does not limit the specific multi-level variable frequency corrosion process.
[0038] Furthermore, the corroded aluminum foil is subjected to a multi-stage chemical treatment, that is, anodization is performed in a specific electrolyte to form a stable aluminum oxide film, which will serve as the dielectric layer of the capacitor.
[0039] Furthermore, the method further includes post-processing the aluminum foil after chemical formation, including steps such as cleaning, drying and cutting, so as to ensure the cleanliness and dimensional accuracy of the aluminum foil, and finally obtain a finished anode foil.
[0040] The cathode foil described in the embodiment of the present invention is an Al2O3-TiO2 composite foil.
[0041] Specifically, the preparation process of the cathode foil of the embodiment of the present invention includes: bare foil-etching-coating-post-treatment. The material for improving the performance of aluminum electrolytic capacitors is prepared by preparing a TiO2 film on the surface of aluminum etched foil. This sandwich structure composite foil can improve the specific capacitance of the capacitor and enhance its mechanical properties and withstand voltage value.
[0042] Specifically, in the coating process, a coating containing nano-TiO2 particles is coated on the surface of the aluminum foil with slight corrosion, and after drying, the binder in the coating is carbonized at high temperature in an oxygen-free environment, and then post-processed to finally obtain a finished cathode foil. The specific volume of the Al2O3-TiO2 composite cathode foil of the present invention is more than 5 times higher than that of the traditional Al2O3 cathode foil, which greatly improves the synthetic specific volume of the electrolytic capacitor.
[0043] The electrolyte of the embodiment of the present invention requires that the water content of the electrolyte is ≤2% and the conductivity is ≥13ms / cm, and it also has good low temperature resistance to ensure the performance and reliability of the aluminum electrolytic capacitor, and to ensure the quality and life. Suitable electrolytes include GBL system electrolytes or ethylene glycol system electrolytes. The electrolyte described in this embodiment is preferably a GBL (γ-butyrolactone) system electrolyte. Compared with the traditional cyclic carbonate system electrolyte, the GBL system electrolyte has better thermal stability and electrochemical properties.
[0044] Generally, the electrolyte of the GBL system includes the following components:
[0045] Solvent: GBL is used as the main solvent and is usually mixed with other solvents (such as carbonates) to improve the performance of the electrolyte. Common solvent combinations include GBL with ethylene carbonate (EC), dimethyl carbonate (DMC), etc. The high dielectric constant and good solubility of GBL make it an ideal solvent for lithium salts.
[0046] Lithium salt: Commonly used lithium salts include lithium hexafluorophosphate (LiPF6) and lithium fluorophosphate (LiFSI). The choice of lithium salt directly affects the conductivity of the electrolyte and the overall performance of the battery. GBL's high donor number enables it to effectively dissolve additives such as LiNO3 and enhance the cycle stability of the battery.
[0047] Additives: In order to improve the performance of the electrolyte, some functional additives are usually added, such as film-forming additives and high-temperature stability additives. For example, LiNO3 can inhibit the growth of lithium dendrites and enhance the safety and cycle life of the battery. In addition, the selection and dosage of additives need to be optimized according to the specific needs of the battery.
[0048] Ratio: The specific ratio of GBL-based electrolyte varies according to the battery type and application scenario. Generally speaking, the volume ratio of GBL can account for more than 50% of the electrolyte, and the concentration of lithium salt is usually around 1M.
[0049] For the present invention, the electrolyte can be a commercially available GBL system electrolyte, which can satisfy the requirements of a water content of ≤2% and a conductivity of ≥13ms / cm and good low temperature performance.
[0050] In other embodiments of the present invention, the electrolyte may also be a commercially available ethylene glycol electrolyte, as long as the water content of the electrolyte is ≤ 2% and the conductivity is ≥ 13 ms / cm.
[0051] The present invention does not limit the specific composition of the electrolyte.
[0052] The liquid shrink aluminum electrolytic capacitor of the embodiment of the present invention also optimizes the electrolytic paper, the thickness of the electrolytic paper is 30-50 μm, and the density is 0.30-0.50 g / cm 3 .
[0053] The manufacturing process of capacitor paper is complex and delicate, and it needs to meet requirements such as high purity, uniformity, mechanical and electrical strength, absorption, and voltage resistance. The key steps include:
[0054] Raw material selection: Select high-quality cellulose raw materials, such as wood pulp, agave fiber, grass fiber, and even special fibers such as Manila hemp fiber. Manila hemp fiber is used in the production of electrolytic capacitor paper because of its high strength, acid resistance, alkali resistance, heat resistance, and water resistance.
[0055] Pulping: The selected raw materials are made into pulp through processes such as cooking and bleaching.
[0056] Beating: The pulp is processed through a beater to adjust the fiber morphology and pulp concentration to achieve the desired physical properties.
[0057] Papermaking: The treated pulp is formed by papermaking on a fourdrinier paper machine to control the concentration of the paper and the uniformity of the pulp.
[0058] Pressing and drying: The pressing and drying processes remove moisture from the paper to form a preliminary paper sheet structure.
[0059] Surface treatment: may include coating, calendering, etc. to improve the smoothness and uniformity of the paper.
[0060] Slitting and curling: Slitting the paper into appropriate width and curling it as needed.
[0061] Quality Control: Throughout the production process, the quality and performance of the paper needs to be strictly tested and controlled to ensure that the high standards required for electrolytic capacitor paper are met.
[0062] Special processing: For ultra-thin electrolytic capacitor paper, special production processes may be required, such as using cellulose microfibrils mixed with pulp, and special beating and drying processes to ensure the strength and pressure resistance of the paper.
[0063] Insulation Treatment: In some cases, electrolytic capacitor paper may require insulation treatment to improve its electrical performance.
[0064] The precise control and optimization of these steps are essential for producing high-quality electrolytic capacitor paper. Through these process steps, electrolytic capacitor paper with different properties can be manufactured to meet the needs of different applications. The present invention does not specifically limit the manufacturing process of electrolytic capacitor paper.
[0065] In practical applications, the thickness and tightness of electrolytic capacitor paper have many specific effects on the performance of the capacitor:
[0066] Capacitance: The thickness of electrolytic capacitor paper directly affects the size of the capacitor. Under the same withstand voltage conditions, generally speaking, the thicker the paper, the larger the core size, and the shorter the length of the anode foil that can be wound, resulting in a relatively smaller product capacitance.
[0067] Equivalent Series Resistance (ESR): The material, thickness, and tightness of electrolytic paper will affect its resistance characteristics, which in turn affects the ESR of the capacitor. Thicker paper may result in higher resistance, which will affect the performance of the capacitor at high frequencies. Lower ESR helps improve the power transfer capability and high-frequency response of the capacitor. Electrolytic paper with low tightness usually has lower losses because its structure is looser, which helps the flow of electrolyte and the migration of ions, thereby reducing the equivalent series resistance (ESR) of the capacitor.
[0068] Absorption: The thickness and tightness of electrolytic paper are closely related to its ability to absorb electrolyte. Paper with moderate thickness can better retain electrolyte, thereby improving the performance and stability of the capacitor. At the same time, the lower the tightness of the electrolytic paper, the better its liquid absorption performance and can absorb more electrolyte. This helps the electrolyte fully infiltrate the electrodes, thereby improving the capacitance and conductivity of the capacitor.
[0069] Mechanical strength: Thickness also affects the mechanical strength of electrolytic paper. Thicker papers generally have better tensile strength and pressure resistance, which are critical for the reliability of capacitors under working conditions. In addition, while low-density papers may provide better liquid absorption and lower losses, they may be inferior in mechanical strength. High-density papers can provide better mechanical strength, which is important for the physical stability and durability of capacitors. Further, high-density papers may provide better voltage resistance performance because their structure is more compact and less susceptible to voltage breakdown.
[0070] Thermal stability: The thickness of electrolytic paper has an impact on its thermal stability. In high temperature or high voltage environments, thicker paper may be more resistant to electrochemical reactions and chemical degradation, thereby increasing the service life of the capacitor.
[0071] Leakage current: The thickness and uniformity of electrolytic paper directly affect the leakage current of the capacitor. Paper with uneven thickness or defects may cause increased leakage current, thus affecting the performance and safety of the capacitor. Electrolytic paper with uniform tightness can provide better electrical performance and reduce the risk of short circuits inside the capacitor.
[0072] Therefore, the material, thickness, and tightness of the electrolytic capacitor paper are important factors affecting the performance of the capacitor. Reasonable thickness and tightness design can significantly improve the electrical performance and mechanical stability of the capacitor. In the embodiment of the present invention, the electrolytic paper is preferably made of Manila hemp fiber. In the embodiment of the present invention, the electrolytic paper is preferably made of Manila hemp fiber, with a thickness of 30 to 50 μm and a tightness of 0.30 to 0.50 g / cm 3 The electrolytic paper under this condition can reduce the loss angle, self-heating and ESR of the electrolytic capacitor.
[0073] The embodiment of the present invention also includes optimizing the guide needle, preferably a low-voltage forming guide needle, with a forming voltage ≥140V.
[0074] Low-voltage formation of guide pins is an important step in the production process of aluminum electrolytic capacitors. It involves electrochemical treatment of aluminum guide pins to form a uniform oxide film with good dielectric properties. This process is critical to the performance and reliability of the capacitor. The following are some key steps and considerations for low-voltage formation of guide pins:
[0075] Guide pin preparation: Before formation, the aluminum guide pin needs to be cleaned to remove oil and impurities on the surface to ensure that the formation of the oxide film is not disturbed.
[0076] Selection of the forming liquid: The formula of the forming liquid has a significant impact on the quality and characteristics of the oxide film. Usually, the forming liquid contains specific chemical components, such as organic acids or their salts, to promote the formation of the oxide film.
[0077] Electrochemical treatment: In the formation tank, the guide needle acts as an anode and electrochemical oxidation is performed by applying voltage. This process requires precise control of voltage, current and time to ensure the uniformity and stability of the oxide film. In this embodiment, the formation voltage is ≥140V, preferably 140V, 150V, 160V.
[0078] Post-processing: After formation, the guide pins need to be cleaned to remove residual formation liquid and then dried. This step is critical to remove moisture and improve the reliability of the capacitor.
[0079] Quality inspection: The formed guide pins need to undergo strict quality inspection, including film thickness, film quality and physical properties of the guide pins, to ensure that they meet the requirements of capacitor manufacturing.
[0080] See also Figure 2 The cathode foil 1, electrolytic paper 3, anode foil 2, positive electrode guide pin 41 and negative electrode guide pin 42 are wound into a capacitor core 10 according to a certain structure, which is then installed in a sleeve 7, and an electrolyte is injected. The capacitor core 10 is sealed with a sealing rubber plug 5 to prevent leakage of the capacitor core 10, and a semi-finished capacitor is obtained. After the capacitor core 10 is installed in the sleeve 7, it is further transferred into an aluminum housing 6 for aging treatment, and then good products are screened out after sorting and testing, and an aluminum electrolytic capacitor is obtained.
[0081] The prepared electrolytic capacitor can be installed on the electronic circuit and then used.
[0082] The casing has two main functions: 1) to identify the product, such as trademark, capacity, voltage, model, temperature, polarity, etc.; 2) to act as an insulator to prevent short circuit and static electricity on the pole shell.
[0083] In the present invention, when the negative electrode guide pin is connected to the cathode foil, the production process is optimized by adding riveted petals, and the area of a single riveted petal needs to be increased by 10% to balance the resistance generated by the riveting.
[0084] It should be noted that in the present invention, the main material of the sealing rubber plug is EPDM, and the sealing rubber plug contains ≥30% IIR by mass, preferably 40% IIR. In the present invention, IIR refers to isobutylene-isoprene rubber, which has the following characteristics:
[0085] Air tightness: IIR has an extremely low gas permeability, which can effectively prevent gas leakage and is suitable for making inner tubes and airtight materials.
[0086] Chemical resistance: It has good resistance to a variety of chemicals (such as acids, alkalis and solvents) and is suitable for lining of chemical equipment.
[0087] Aging resistance: IIR is highly resistant to ozone and oxygen and can maintain performance in harsh environments.
[0088] Elasticity and shock absorption: Although the elasticity is low at room temperature, it increases significantly at high temperatures and has good shock absorption properties.
[0089] Electrical insulation: IIR has better electrical insulation properties than most synthetic rubbers and is suitable for use as insulation for wires and cables.
[0090] Adding isobutylene-isoprene rubber to the sealing plug can improve the following properties of the sealing plug:
[0091] Enhanced air tightness: IIR's low air permeability helps improve the air tightness of the seal and reduce the risk of gas leakage.
[0092] Heat aging resistance: IIR's heat aging resistance can extend the service life of the sealing ring and maintain a stable sealing effect in a high temperature environment.
[0093] Chemical resistance: IIR has good resistance to a variety of chemicals, including acids, bases and organic solvents, which enables the seal to maintain good sealing performance in harsh chemical environments.
[0094] Improved mechanical properties: The addition of IIR can improve the tensile strength, tensile stress and elasticity of the seal ring, which is essential for withstanding high-pressure environments.
[0095] Dimensional stability: IIR's low water absorption helps maintain the dimensional stability of the seal ring and prevents expansion or deformation caused by water absorption.
[0096] Electrical Insulation Properties: IIR's electrical insulation properties are very useful for sealing applications where electrical insulation is required.
[0097] Therefore, the sealing rubber plug in the present invention is required to have a hardness change of no more than 5% after being placed in an environment of 125° C. for 48 hours. Among the materials of the sealing rubber plug, a sealing rubber plug containing a mass fraction of ≥30% IIR is preferred.
[0098] For example, a sealing rubber plug containing 40% IIR by mass is selected.
[0099] In other embodiments, a sealing rubber plug containing 50% by mass of IIR is selected.
[0100] The present invention does not limit the specific composition of the sealing rubber plug, as long as the mass fraction is ≥30% IIR and the performance is such that the hardness change of the rubber plug does not exceed 5% after being placed in an environment of 125°C for 48 hours. Those skilled in the art can select commercially available sealing rubber plugs with good stability according to the above requirements.
[0101] The optimization of the sealing rubber plug of the present invention is helpful to improve the reliability of the aluminum electrolytic capacitor.
[0102] The working voltage of the liquid shrinkage aluminum electrolytic capacitor prepared according to the embodiment of the present invention is ≤25WV.
[0103] Case 1 Preparation of leaded liquid aluminum electrolytic capacitors with specifications of 25V 100μF
[0104] It should be noted that the material matching size of aluminum electrolytic capacitors is related to the design matching of anode foil (thickness, withstand voltage, specific capacitance), cathode foil (thickness, specific capacitance), and electrolytic paper (thickness). The rated working voltage of the product is determined, and the withstand voltage selection of each material is relatively fixed.
[0105] The length calculation formula of the capacitor core is: L = [(C 阳 +C 阴 ) / (C 阳 *C 阴 )】*C 标 / d 阳极箔宽度 ;
[0106] C 阳 : refers to the specific volume of anode foil;
[0107] C 阴 : refers to the specific volume of cathode foil;
[0108] C 标 : Refers to the nominal capacity of the capacitor.
[0109] Generally speaking, the thicker the anode foil, the higher the specific capacity.
[0110] Example 1
[0111] The diameter×height of the lead-type liquid aluminum electrolytic capacitor prepared in Example 1 is 6.3 mm×11 mm. The specifications of the cathode foil, anode foil, electrolytic paper, electrolyte, guide pin, sealing rubber plug, etc. used are as follows:
[0112] Anode foil: thickness is 80±5%μm.
[0113] Cathode foil: thickness 50±8%μm, specific capacity 400~450μF / cm 2 .
[0114] Electrolytic paper: thickness 50±8%μm, density 0.5g / cm 3 , Manila hemp fiber electrolytic paper.
[0115] Considering the cost, the electrolyte of this embodiment is a commercially available ethylene glycol electrolyte, which has a water content of ≤2% and a conductivity of ≥13ms / cm and has good low temperature performance.
[0116] The guide needle is a low-voltage forming guide needle, and the forming voltage is ≥140V.
[0117] The sealing rubber plug of the present embodiment is made of EPDM rubber. After being placed in an environment of 125° C. for 48 hours, the hardness change of the rubber plug does not exceed 5%.
[0118] Example 2
[0119] In this embodiment, the lead-type liquid aluminum electrolytic capacitor prepared in Example 1 is optimized to reduce the volume while keeping the capacitor specifications unchanged. The specifications of the cathode foil, anode foil, electrolytic paper, electrolyte, guide pin, sealing rubber plug, etc. used are as follows:
[0120] Anode foil: thickness is 85±5%μm.
[0121] Cathode foil: thickness 50±8%μm, specific capacity 400~450μF / cm 2 .
[0122] Electrolytic paper: thickness 50±8%μm, density 0.5g / cm 3 , Manila hemp fiber electrolytic paper.
[0123] The electrolyte of this embodiment is a commercially available ethylene glycol electrolyte with a water content of ≤2% and a conductivity of ≥13 ms / cm.
[0124] The guide needle is a low-voltage forming guide needle, and the forming voltage is ≥140V.
[0125] The sealing rubber plug of the present embodiment is made of EPDM. Meanwhile, after being placed in an environment of 125° C. for 48 hours, the change in hardness of the rubber plug does not exceed 5%.
[0126] The diameter×height of the lead-type liquid aluminum electrolytic capacitor prepared in this embodiment is 6.3 mm×7 mm, and compared with Embodiment 1, the volume is reduced by 36.36%.
[0127] Example 3
[0128] In this embodiment, the lead-type liquid aluminum electrolytic capacitor prepared in Example 1 is optimized to reduce the volume while keeping the capacitor specifications unchanged. The specifications of the cathode foil, anode foil, electrolytic paper, electrolyte, guide pin, sealing rubber plug, etc. used are as follows:
[0129] Anode foil: thickness is 105±5%μm.
[0130] Cathode foil: thickness 50±8%μm, specific capacity 400~450μF / cm 2 .
[0131] Electrolytic paper: thickness 40±8%μm, density 0.5g / cm 3 , Manila hemp fiber electrolytic paper.
[0132] The electrolyte of this embodiment is a commercially available ethylene glycol system electrolyte, which can satisfy the requirements that the water content of the electrolyte is ≤2% and the conductivity is ≥13ms / cm, and has good low-temperature performance.
[0133] The guide needle is a low-voltage forming guide needle, and the forming voltage is ≥140V.
[0134] The sealing rubber plug of the present embodiment is made of EPDM. Meanwhile, after being placed in an environment of 125° C. for 48 hours, the change in hardness of the rubber plug does not exceed 5%.
[0135] The lead-type liquid aluminum electrolytic capacitor prepared in this embodiment has a diameter×height of 5 mm×11 mm, and its volume is reduced by 37.01% compared with that of Embodiment 1.
[0136] Example 4
[0137] In this embodiment, the lead-type liquid aluminum electrolytic capacitor prepared in Example 1 is optimized to reduce its volume while keeping the capacitor specifications unchanged. The specifications of the cathode foil, anode foil, electrolytic paper, electrolyte, guide pin, sealing rubber plug, etc. used are as follows:
[0138] Anode foil: thickness is 105±5%μm.
[0139] Cathode foil: thickness 30±8%μm, specific capacity 3000~4000μF / cm 2 .
[0140] Electrolytic paper: thickness 40±8%μm, density 0.4g / cm 3 , Manila hemp fiber electrolytic paper.
[0141] The electrolyte of this embodiment is a commercially available ethylene glycol electrolyte with a water content of ≤2% and a conductivity of ≥13 ms / cm.
[0142] The guide needle is a low-voltage forming guide needle, and the forming voltage is ≥140V.
[0143] The sealing rubber plug of the present embodiment is made of EPDM. Meanwhile, after being placed in an environment of 125° C. for 48 hours, the change in hardness of the rubber plug does not exceed 5%.
[0144] The diameter×height of the lead-type liquid aluminum electrolytic capacitor prepared in this embodiment is 4 mm×11 mm, and compared with Embodiment 1, the volume is reduced by 59.69%.
[0145] From the above results, it can be seen that by selecting thick anode foil, choosing cathode foil with large specific capacitance, and optimizing the specifications of electrolytic paper, electrolyte, guide pins, etc., a smaller lead-type liquid aluminum electrolytic capacitor can be obtained under the same capacitance specifications.
[0146] Case 2: Preparation of 16V 470μF SMD Liquid Aluminum Electrolytic Capacitor
[0147] Example 5
[0148] The diameter×height of the SMD liquid aluminum electrolytic capacitor prepared in Example 5 is 8.0 mm×10.5 mm. The specifications of the cathode foil, anode foil, electrolytic paper, electrolyte, guide pin, sealing rubber plug, etc. used are as follows:
[0149] Anode foil: thickness 100±5%μm.
[0150] Cathode foil: thickness 50±8%μm, specific capacity 400~450μF / cm 2 .
[0151] Electrolytic paper: thickness 40±8%μm, density 0.5g / cm 3 , Manila hemp fiber electrolytic paper.
[0152] The electrolyte is a commercially available GBL system electrolyte, which can satisfy the requirements that the water content of the electrolyte is ≤2% and the conductivity is ≥13ms / cm, and has good low-temperature performance.
[0153] The guide needle is a low-voltage forming guide needle, and the forming voltage is ≥140V.
[0154] The sealing rubber plug contains 40% by mass of IIR. Meanwhile, after being placed at 125° C. for 48 hours, the change in hardness of the rubber plug does not exceed 5%.
[0155] Example 6
[0156] In this embodiment, the size of the SMD liquid aluminum electrolytic capacitor prepared in Example 5 is optimized while the capacitor specifications remain unchanged. The specifications of the cathode foil, anode foil, electrolytic paper, electrolyte, guide pin, sealing rubber plug, etc. used are as follows:
[0157] Anode foil: thickness is 120±5%μm.
[0158] Cathode foil: thickness 30±8%μm, specific capacity 3000~4000μF / cm 2 .
[0159] Electrolytic paper: thickness 30±8%μm, density 0.4g / cm 3 , Manila hemp fiber electrolytic paper.
[0160] The electrolyte is a commercially available GBL system electrolyte, which can satisfy the requirements that the water content of the electrolyte is ≤2% and the conductivity is ≥13ms / cm, and has good low-temperature performance.
[0161] The guide needle is a low-voltage forming guide needle, and the forming voltage is ≥140V.
[0162] The sealing rubber plug contains 40% by mass of IIR. Meanwhile, after being placed at 125° C. for 48 hours, the change in hardness of the rubber plug does not exceed 5%.
[0163] The diameter×height of the SMD liquid aluminum electrolytic capacitor prepared in this embodiment is 6.3 mm×7.7 mm, and compared with Embodiment 5, the volume is reduced by 54.52%.
[0164] The above results show that the liquid reduced aluminum electrolytic capacitor provided by the present invention can effectively reduce the size of the aluminum electrolytic capacitor by more than 20% while keeping the voltage and capacity of the aluminum electrolytic capacitor unchanged by optimizing the specifications of components such as the cathode foil, anode foil, electrolytic paper, and electrolyte, thereby ensuring miniaturization without sacrificing performance.
[0165] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0166] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A liquid shrink aluminum electrolytic capacitor, characterized in that: Including anode foil, cathode foil, electrolyte and electrolytic paper; The anode foil is a multi-stage frequency conversion corrosion aluminum foil; The cathode foil is an Al2O3-TiO2 composite foil; The water content of the electrolyte is ≤2% and the conductivity is ≥13ms / cm; The thickness of the electrolytic paper is 30-50 μm, and the density is 0.30-0.50 g / cm 3 ; The working voltage of the liquid shrink aluminum electrolytic capacitor is ≤25WV.
2. The liquid-shrink aluminum electrolytic capacitor according to claim 1, characterized in that: It also includes a guide needle, which is a low-voltage forming guide needle with a forming voltage ≥140V.
3. The liquid-shrink aluminum electrolytic capacitor according to claim 1, characterized in that: The electrolyte is a GBL system electrolyte or an ethylene glycol system electrolyte.
4. The liquid shrinkage aluminum electrolytic capacitor according to claim 1, characterized in that: The material of the electrolytic paper is Manila hemp fiber.
5. The liquid-shrink aluminum electrolytic capacitor according to claim 1, characterized in that: The liquid shrink aluminum electrolytic capacitor also includes a sealing rubber plug. After the sealing rubber plug is placed in an environment of 125° C. for 48 hours, the change in hardness of the rubber plug does not exceed 5%.
6. The liquid shrinkage aluminum electrolytic capacitor according to claim 5, characterized in that: The sealing rubber plug contains IIR in an amount of ≥30% by mass.
7. The liquid-shrink aluminum electrolytic capacitor according to claim 1, characterized in that: The preparation process of the anode foil includes: plain foil-multi-stage variable frequency etching-multi-stage chemical formation treatment; wherein, when the multi-stage variable frequency etching process is performed, the frequency range of the alternating current is between 5 and 40 Hz, and the frequency values of each stage are different from each other.
8. The liquid-shrink aluminum electrolytic capacitor according to claim 7, characterized in that: The light foil process stage also includes annealing treatment, and the annealing temperature is 400-500°C.
9. The liquid-shrink aluminum electrolytic capacitor according to claim 1, characterized in that: The Al2O3-TiO2 composite foil is prepared by coating TiO2 nanoparticles on the surface of an aluminum corrosion foil.
10. The liquid shrinkage aluminum electrolytic capacitor according to any one of claims 1 to 9, characterized in that: For a liquid reduced aluminum electrolytic capacitor with a working voltage of 25WV and a capacitance of 100μF, the diameter×height dimensions are less than 6.3mm×11mm; for a liquid reduced aluminum electrolytic capacitor with a working voltage of 16WV and a capacitance of 470μF, the diameter×height dimensions are less than 8mm×10.5mm.
